2016
DOI: 10.1093/cid/ciw098
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Duration of Antibiotic Therapy in Patients With Hematogenous Vertebral Osteomyelitis at Low Risk and High Risk of Recurrence

Abstract: Antibiotic therapy of prolonged duration (≥8 weeks) should be given to patients with HVO at high risk of recurrence. For low-risk patients, a shorter duration (6-8 weeks) of pathogen-directed antibiotic therapy may be sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 35 publications
7
90
1
4
Order By: Relevance
“…This is of critical importance in patients who require valve surgery because a persistent source of infection may serve as a source from which a recently placed prosthetic valve or annuloplasty ring becomes infected 101,102 . Some metastatic foci, such as vertebral osteomyelitis, may require additional antibiotic therapy beyond what is typically indicated for IE 179 . There is currently insufficient evidence to recommend specific imaging strategies to look for metastatic foci in all patients with IE.…”
Section: Managementmentioning
confidence: 99%
“…This is of critical importance in patients who require valve surgery because a persistent source of infection may serve as a source from which a recently placed prosthetic valve or annuloplasty ring becomes infected 101,102 . Some metastatic foci, such as vertebral osteomyelitis, may require additional antibiotic therapy beyond what is typically indicated for IE 179 . There is currently insufficient evidence to recommend specific imaging strategies to look for metastatic foci in all patients with IE.…”
Section: Managementmentioning
confidence: 99%
“…However, there was evidence that advanced age (≥ 75 years) and S. aureus are risk factors for the failure of antibiotic therapy. Another retrospective study (n = 314) identified risk factors for recurrence, classified patients into high-risk and low-risk groups, and correlated treatment success with treatment duration (39). The mean time to relapse was given as 5 weeks (1.5 weeks−30 months), and infections with methicillin-resistant S. aureus (MRSA), undrained paravertebral and psoas abscesses, as well as severe kidney failure were identified as independent risk factors.…”
Section: Signs Of Paravertebral/epidural Inflammationmentioning
confidence: 99%
“…The recurrence rates reported in the previous literatures have varied greatly. McHenry et al [15] reported a recurrence rate of 14% in 253 patients; Park et al [16] of 9.9% in 314 patients; and Kim et al [14] of 6.6% in 151 patients. Unfortunately, data to guide the optimal duration of antibiotic therapy related to the recurrence of PVO are insu cient [7,17,18].…”
Section: Discussionmentioning
confidence: 98%